Lanthanide-Catalyzed Oxidative С–O Coupling of 1,3-Dicarbonyl Compounds with Diacyl Peroxides - Terent’ev, Alexander O.; Vil’, Vera A.; Nikishin, Gennady I.; Adam, Waldemar (Synlett, 2015)
The lanthanide-catalyzed oxidative C–O coupling of α-substituted 1,3-dicarbonyl compounds with diacyl peroxides (act both as oxidant and oxygen substituent) affords oxygen-functionalized adducts in up to 94% yield. The products of this convenient and efficient transformation serve as potentially valuable precursors for the synthesis of natural products and pharmaceuticals.
Keywords: С–O coupling; dicarbonyl compounds; peroxides; lanthanide; catalysis